I.JAVAKHISHVILI ABOUT THE GEORGIAN PARLIAMENTARY SYSTEM “DARBAZI” AND “DARBAZOBA” (Law and world, 2017)
According to some georgoian scientists the basis of Constitutional Justice Science was founded in the early- feudal Georgia. The great doctrine by Sharl-Lui Montesquieu about the distribution of power is commonly known. We pay attention to the fact that in the United Kingdom at the head of the country was the King – supreme sovereign. We have already mentioned that the battle between nobles was characteristic to our country. The central, authoritative government had to ﬁ ght against nobles who were trying to limit its power. Ivane Javakhishvili describes the details of this battle. Also he widely touches upon the descriptions of the rules of such institutions as “Darbazoba” and Darbazi. This article also touches upon the issue “unanimous will and concord”. It was a compromise-settlement of the King who agreed to govern the state jointly with other members of higher nobility. The King had to take the decisions of the “Darbazi” into consideration and would have to endorse them, so “Karavi” was governing the country, the King remained as an executive. The author means, that the political programme drawn up by Kultu Arslani and his supporters were to create a representative state body with powers to pass decisions on all important affairs within state. The process of political development of Georgian people, which has great traditions, is revealed in Kultu-Arslani’s political opposition and programme, when the supporters, instead of bloody battle, showed the culture of political compromise and high state thought. The demand of pitching a tent in Isani included the signs of power division, constitutional monarchy and Parliamentary thinking.